The availability of full match sibling donors and feasibility of allogeneic bone marrow transplantation in Brazil - Eid K.A.B.; Miranda E.C.M.; Vigorito A.C.; Aranha F.J.P.; Oliveira G.B.; De Souza C.A. (Brazilian Journal of Medical and Biological Research, 2003)
The feasibility of allogeneic bone marrow transplantation (alloBMT) in a developing country has not yet been demonstrated. Many adverse factors including social and economic limitations may reduce the overall results of this complex and expensive procedure. Our objective was to characterize the most important clinical, social and economic features of candidates for transplantation and their potential donors as well as the influence of these factors on overall survival in a retrospective and exploratory analysis at a university hospital. From July 1993 to July 2001, candidates for BMT were referred to the Bone Marrow Transplantation Unit by Hematology and Oncology Centers from several regions of Brazil. A total of 1138 patients were referred to us as candidates for alloBMT. Median age was 25 years (range: 2 months-60 years), 684 (60.1%) were males and 454 (39.9%) were females. The clinical indications were severe aplastic anemia and hematological malignancies. From the total of 1138 patients, 923 had HLA-typing; 497/923 (53.8%) candidates had full match donors; 352/1138 (30.8%) were eligible for alloBMT. Only 235 of 352 (66.7%) were transplanted. Schooling was 1st to 8th grade for 123/235 (52.3%); monthly family income ranged from US$60 (7%) to more than US$400 (36%). Overall survival for patients with chronic myeloid leukemia, severe aplastic anemia and acute myeloid leukemia was 58, 60 and 30%, respectively. Thus, overall survival rates for the most frequent hematological diseases were similar to those reported in the International Registry, except for acute myeloid leukemia. This descriptive and exploratory analysis suggests the feasibility of alloBMT in a developing country like Brazil.